PENGARUH PELUANG KERJA, SIKAP, DAN KONTROL PERILAKU TERHADAP NIAT MAHASISWA MENGAMBIL JURUSAN AKUNTANSI - Desy Cindy Putri Pertiwi Pertiwi; Mortigor Afrizal Purba (LPPM Universitas Putera Batam, 2026)
Many students remain unsure about choosing an accounting major due to a lack of knowledge about career opportunities in the accounting sector. This uncertainty is also influenced by negative attitudes, such as the perception that accounting is complex and requires high-skill skills. Furthermore, students' perceptions of low behavioral control, such as a lack of confidence in their abilities and limited support from their environment, also hinder their intention to major in accounting. In this context, this study aims to assess the impact of job opportunities, attitudes, and behavioral control on students' intentions to major in accounting. The approach applied in this study was quantitative, with a total population of 100 students from accounting study programs in Batam. To select a representative sample, the study applied the Slovin formula, resulting in 97 respondents. Data collection was carried out by distributing questionnaires that had been previously tested to ensure their validity and reliability. After that, the information was analyzed using multiple linear regression. These results indicate that job opportunities have a significant influence on students' intention to major in accounting, attitudes also have a significant influence on students' intention to major in accounting, and behavioral control has a significant influence on students' intention to major in accounting. Based on the results of the tests conducted simultaneously in this study, it can be concluded that the three independent variables (job opportunities, attitudes, and behavioral control) have a simultaneous influence on accounting students' interest.